The Wiley handbook on what works for offenders with intellectual and developmental disabilities: an evidence-based approach to theory, assessment, and treatment - Lindsay, William R.; Craig, Leam A.; Griffiths, Dorothy (Wiley Blackwell, 2020)
Introduction and overview / Leam A. Craig, William R. Lindsay and Dorothy M. Griffiths -- The ethics of evidence-based practice / Dorothy M. Griffiths -- Protecting the rights of people with intellectual disabilities in correctional settings / Frank Lambrick, Astrid Birgden, Chelsea Troutman & Danielle McLeod -- Behavioural and cognitive phenotypes in genetic disorders associated with offending / Lauren J. Rice, Stewart L. Einfeld & Patricia Howlin -- Diagnosis of personality disorder in offenders with intellectual and developmental disabilities / Nigel Beail -- Assessment for anger and violence / Paul Willner, Andrew Jahoda & Ken McMahon -- Assessment for inappropriate sexual behaviour / Lesley R. Steptoe & Amanda M. Michie -- Assessment for social problem-solving, social information processing and criminal thinking / Peter E. Langdon -- Assessment of alcohol use disorder and alcohol-related offending behaviour / Joanne E.L. VanDerNagel, Neomi van Duijvenbode & Robert Didden -- Assessing people with intellectual disabilities who have engaged in fire setting / Samuel J. Tromans, Verity Chester & Regi T. Alexander -- Assessment for emotional difficulties related to offending / Deborah Richards, Tyler Oswald & J. Paul Fedoroff -- Using a multi-component model in the assessment of persons with intellectual disabilities and problems in sexual behaviour / Robin J. Wilson, Stephanie Ioannou & Kendra Thomas -- Supporting people with intellectual and developmental disabilities leaving prison / Kathy Ellem, Michelle Denton & Danielle Davidson -- Prison based programmes for people with intellectual and developmental disabilities / Philip Snoyman, Berindah Aicken & Jayson Ware -- Treatment of anger and violence in individuals with intellectual disability / Robert Didden, Henk Nijman, Monique Delforterie & Marije Keulen-De Vos -- Treatment for inappropriate sexual behaviour for people with intellectual and developmental disabilities / Leam A. Craig -- Treatment for social problem solving and criminal thinking / Susan Hayes -- Treating substance misuses among offenders with intellectual and developmental disabilities / Daniel Newton & Jane McGillivary -- Treatment for emotional difficulties related to offending for people with IDD / Paul Oxnam & Emma Gardner -- Treatment outcomes for people with autistic spectrum disorder in forensic settings / Peter Sturmey -- Pharmacological approaches for offenders with intellectual and developmental disabilities / Daniel Turner & Peer Briken -- Future directions and requirements for offenders with intellectual and developmental disabilities / Dorothy M. Griffiths & Leam A. Craig.